Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan PhET (Physics Education Technology) Terhadap Hasil Belajar Fisika Siswa - Eka Rahayu Febniani; Muhammad Taufik; Hikmawati Hikmawati; Susilawati Susilawati (Kappa Journal, 2022)
This study aims to determine the effect of guided inquiry learning model assisted by PhET (Physics Education Technology) on high school students' physics learning outcomes. The type of research used is quasi-experimental with pretest-posttest control group design. The population of this study were all students of class X MIA at MA PLUS NURUL ISLAM Sekarbela Mataram. The sample of this study was class X MIA 1 and X MIA 2 which amounted to 40 students with a sampling technique using the saturated sample technique. The sample used in this study was class X MIA-1 as an experimental class which amounted to 20 students and class X MIA -2 as the control class with a total of 20 students. Before being given treatment, both samples were given an initial test to determine their initial ability. Based on the results of the homogeneity test of the initial test, both samples have the same initial ability. The results of the final test of student learning outcomes obtained the average value of the experimental class 69.25 with the highest score of 85 and the average value of the control class 55 with the highest score of 75. The research hypothesis was tested by polled variance t-test with a significance level of 5%, and the results obtained tcount = 4.18, while ttable = 2.02. Based on these results, it means that tcount is greater than ttable, so H0 is rejected. Thus, it can be concluded that the guided inquiry learning model assisted by PhET (Physics Education Technology) has an effect on high school students' physics learning outcomes.